Reform Israeli Female Rabbis Perform Community Leadership - Ben-Lulu, Elazar (The journal of religion & society, 2017)
This article analyzes leadership performances of Israeli women serving as reform rabbis. The writer examines the ways in which these women construct the pattern of their religious leadership, the meanings they embed into the different practices they lead in their communities, and their unique conceptualizations of the role of female community rabbis. Reform female rabbi, who are also referred to as "rabba," are excluded and discriminated against in Israel as leaders of communities overtly delegitimized by the government. Their unstable social status allows them great freedom to act and interpret the operational definition of Israeli community rabbinate. The female Rabbis’ stories are a product of a broader process of social change in women’s status in modern society in general and in Israeli society in particular.